Peningkatan Motivasi dan Hasil Belajar Peserta Didik Pada Pembelajaran Diskusi Isu Sosiosaintifik Melalui Kunjungan Lapangan - Nabila Salwa Mutia; Yanti Herlanti; Evi Muliyah (Department of Biology Education UIN Sunan Gunung Djati Bandung, 2026)
The Bogor Botanical Gardens possess considerable potential as a learning resource; however, only a limited number of schools utilise this opportunity. This study aims to examine the impact of the field trip method at the Bogor Botanical Gardens on students’ motivation and learning outcomes in the topic Ecosystem Components and Their Interactions. A quasi-experimental design was employed. The participants comprised 22 male and 35 female students, divided into two groups: the control and the experimental groups. The experimental group participated in a field trip, while the control group followed the conventional method typically used by teachers, namely group discussions. During the third session, both groups engaged in discussions based on socioscientific issues. The results indicated no significant difference in overall learning outcomes between the two groups. However, an analysis using Bloom’s taxonomy showed that the experimental group performed better in the domains of understanding (C2) and application (C3). In contrast, the control group excelled in the analysis domain (C4). Similarly, there was no significant difference in learning motivation between the two groups. Nonetheless, students in the experimental group displayed enthusiasm, expressed enjoyment, and found the materials easier to comprehend during field-based learning activities. Based on these findings, field trips to the Bogor Botanical Gardens may enhance the affective domain and foster more conscious, meaningful, and enjoyable learning experiences.